Big Five Audits and Accounting Fraud - LENNOX, CLIVE; PITTMAN, JEFFREY A. (Contemporary Accounting Research, 2010)
We examine the association between Big Five audits and the incidence of accounting frauds allegedly committed by U.S. public companies between 1981 and 2001. Many commentators argue that the prominent financial reporting failures that led to major corporate governance reforms cast serious doubt on whether the large public accounting firms continue to supply relatively high‐quality audits, especially in recent years. However, in unmatched and matched samples, we provide strong, robust evidence that fraudulent financial reporting becomes less likely with the presence of a Big Five auditor. Importantly, time‐series tests suggest that the Big Five are consistently associated with a lower incidence of fraudulent accounting, including in the last five years of our sample period when the number of frauds soared. Moreover, we find evidence implying that these relations are causal rather than an artifact of endogeneity in auditor choice.